The Role of Smart-Phone Based Interactive Technology in Marketing - Suhaimi Mohd Yusof, Muhammad; Hota, Sweta Leena; Atalay Şimşek, Sidar; Champatiray, Manisha Yagyaseni (International Journal of Interactive Mobile Technologies (iJIM), 2025)
The role of smartphone-based interactive technologies, like WhatsApp, in marketing has gained increasing attention because businesses seek more personalised and direct communication channels with consumers. WhatsApp is a widely used messaging application that positively contributes to digital marketing strategies and influences consumer behaviour. The research aims to study the types of interactive technologies used in mobile marketing, particularly WhatsApp, and their impact on consumer behaviour. The analysis includes the theoretical frameworks of WhatsApp marketing as a modern digital approach that provides different advantages in promoting products and services across different sectors. Additionally, the features, tools, and strategies linked with WhatsApp marketing are presented in an explanatory manner and described thoroughly, along with the advantages and disadvantages of its use. Further explanation is provided on consumer behaviour, particularly examining the way WhatsApp marketing drives the purchasing process and decision-making of consumers. The study investigates various marketing practices using WhatsApp, including customer engagement, relationship building, realtime support, and targeted promotional campaigns. The systematic review synthesises existing literature to identify the advantages of WhatsApp marketing, like the high engagement rates, cost-effectiveness, and enhanced customer trust, along with challenges including privacy concerns and message fatigue. A discussion follows on the key points that marketers and business managers consider while integrating WhatsApp into their digital marketing strategies by focusing on its value in enhancing customer engagement, loyalty, and brand interaction.